PROSPECTIVE TEACHERS’ PERCEPTION OF RELIGIOUS IDENTITY IN TERMS OF DIFFERENT IDENTITY TYPES - Namli Altintas, Irem; Mertol, Huseyin; Celikkol, Omer (International Online Journal of Education and Teaching, 2021)
In its simplest sense, identity is the answer to the question, ‘Who am I?’ In other words, identity is a concept that has different meanings from the concepts of personality, self, and selfdom. Identity distinguishes the individual from other individuals, but it also unites individuals with other individuals with similar characteristics. This study aims to investigate according to different variables the identity perceptions of prospective teachers studying in different departments of faculties of education. To this end, the study enrolled 78 male and 228 female students from three different departments (Social Studies Teaching, Classroom Teaching, and Science Teaching). The “Identity Attitudes Scale” developed by Yazıcı (2016) and the “Moral Identity Questionnaire” adapted to Turkish by Sarıçam and Çelik (2018) were applied to the participating students. The study employed the relational screening model. In the analysis of the data, T-test and ANOVA were used to analyze the variables of identity types in terms of socioeconomic backgrounds and gender types. Also, multiple regression analysis was used to explore to what extent identity types predicted religious identity. The analysis results revealed that religious identity perceptions differed depending on socioeconomic levels but not on gender. Besides, it was concluded that prospective teachers’ ethnic and moral identity perceptions did not correlate with their religious identity perceptions, but their political, national, and sexual identity perceptions predicted their religious identity. Considering the overall results obtained in this study, it can be concluded that current curricula of faculties of education fail to equip prospective teachers with the skill of developing a unique identity and that prospective teachers maintain prevalent social attitudes instead of developing personal attitudes.